Risk factors for acute ischaemic stroke in young adults in South India. Issue 9 (12th January 2007) - Lipska, K; Sylaja, P N; Sarma, P S; Thankappan, K R; Kutty, V R; Vasan, R S; Radhakrishnan, K
Abstract : Background: Stroke is a leading cause of death and disability in developing countries, afflicting individuals at a young age. The contribution of established vascular risk factors to ischaemic stroke in young adults has not been evaluated systematically in Indians. Methods: We conducted a case control study in 214 South Indian patients with first acute ischaemic stroke that occurred between the ages of 15 and 45 years, 99 age and sex matched hospital controls and 96 community controls. We compared the prevalence of the following risk factors: smoking, elevated blood pressure, high fasting blood glucose and abnormal lipids. Results: Compared with community controls, stroke patients had a higher prevalence of smoking (multivariable adjusted odds ratio (OR) 7.77, 95% CI 1.93 to 31.27), higher systolic blood pressure (OR per SD increment of 1.88, 95% CI 1.01 to 3.49) and fasting blood glucose (OR per SD increment of 4.55, 95% CI 1.63 to 12.67), but lower high density lipoprotein (HDL) cholesterol (OR per SD increment of 0.17, 95% CI 0.09 to 0.30). Compared with hospital controls, stroke patients had a higher prevalence of smoking (OR 3.95, 95% CI 1.61 to 9.71) and lower HDL cholesterol (OR per SD increment 0.27, 95% CI 0.17 to 0.44). The presence of ⩾3 metabolic syndrome components was associated strongly with stroke (OR 4.76, 95% CI 1.93 to 11.76; OR 2.09, 95% CI 1.06 to 4.13) compared with community and hospital controls. Conclusions: Key components of the metabolic syndrome and smoking are associated with ischaemic stroke in young South Indian adults. Our observations underscore the importance of targeting adolescents and young adults for screening and prevention to reduce the burden of ischaemic stroke in young adults.